FONEM ANAK: DESAIN PEMEROLEHAN BAHASA PERTAMA (Studi Kasus Tentang Pemerolehan Fonem Anak Pada Periode Praoperasional) - PUTU ADITYA ANTARA (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2017)
This study aims to determine the phoneme acquisition period preoperational child at the age of 34 years. The subjects were children of a family that was in Rawamangun, Pulo Gadung. The collection of data obtained with longitudinal observations in 2012. The data were analyzed using content analysis (content analysis). The study concluded: 1) Children aged 3 years and 2 months (ages 34 years) has mastered all vowel phonemes Indonesian. Variations allophonic also been heard. Phonemes which has been controlled children aged two to three years in terms of phonology show some interesting things. It was found that children aged two to three years are already familiar with the vowel [a], [i] , [u], [e], [o]. 2) Likewise with consonant phonemes, children aged 34 years has been able to say almost all consonant phonemes; like the phoneme / b /, / c /, / d /, / f /, / g /, / h /, / j /, / k /, / l /, / m /, / n /, / p /, / q /, / r /, / s /, / t /, / w /, / y / has sounded clearly in the child’s speech. Of the consonant phonemes that have been heard in the speech of children, there are two phonemes that sound is not too obvious, namely the phoneme / d / and / r /; for the phoneme / r / in so many words actually changed the sound into / l /. 3) There are only three consonant phonemes that do not appear in the speech of children (as in speech context 16 above) that is / v /, / x /, and / z /. Of course, lack the pop three consonant phonemes in the speech of children can not be automatically declared that children of this age can not say, because by chance in a speech that was taped there is no word which contains all three elements of the consonant phonemes. 4) In the speech of children aged 3ars there is a process monoftongisasi, alteration or replacement of consonant phonemes, enforced disappearances even phoneme syllables. 5) the double consonant phonemes or clusters yet sounds like words / flood / mbah intention, and word / tub / ya mean.